2013
DOI: 10.1186/2193-1801-2-640
|View full text |Cite
|
Sign up to set email alerts
|

Generation and selection of anti-flagellin monoclonal antibodies useful for serotyping Salmonella enterica

Abstract: In developing countries, bacterial acute gastroenteritis continues to be an important cause of morbidity and mortality among young children. Salmonellosis constitutes a major cause of infectious enteritis worldwide, most of them associated to the consumption of contaminated food products. Traditionally, Salmonella has been classified in serovars based on varieties of O and H surface antigens. In the present work we generated and characterized a panel of anti-flagellin monoclonal antibodies (MAbs) in order to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Conceivably, this cross-reactivity of the pan mAb (P4D9) was due to the contribution of N or C terminus conserved epitopes of flagellin protein, since this mAb was unable to bind to the variable middle region of flagellin from both S. typhi and S. typhimurium. This phenomenon has also been reported earlier [47]. Additionally, enhanced specificity in antibody detection, by middle region, has been exploited against S. enterica serotype Enteriditis, in poultry [50,51], and in case of S. enterica serovar Brandenburg (S. brandenburg) infection, in sheep [52].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Conceivably, this cross-reactivity of the pan mAb (P4D9) was due to the contribution of N or C terminus conserved epitopes of flagellin protein, since this mAb was unable to bind to the variable middle region of flagellin from both S. typhi and S. typhimurium. This phenomenon has also been reported earlier [47]. Additionally, enhanced specificity in antibody detection, by middle region, has been exploited against S. enterica serotype Enteriditis, in poultry [50,51], and in case of S. enterica serovar Brandenburg (S. brandenburg) infection, in sheep [52].…”
Section: Discussionmentioning
confidence: 66%
“…Isolated native flagellin from bacteria was immunogenic and elicited generation of four highly specific monoclonal antibodies, against S. typhi flagellin protein. Earlier reports showed isolation of native flagellin of *52 kDa from Salmonella culture [41][42][43][44][45] and production of anti-flagellin monoclonal antibodies [42,46,47]. We have also isolated genomic DNA, from the clinical isolate, to perform PCR amplification of fliC gene encoding phase 1-d flagellin.…”
Section: Discussionmentioning
confidence: 98%
“…SDS-PAGE analysis along expression and purification process of the chimeric protein BLS-FliC131 indicated that the monomeric protein has the expected molecular weight of 52 kDa. The BLS-FliC131 chimeric protein is recognized by previously described anti-flagellin and anti-BLS monoclonal antibodies, 14,28 as shown by Western blot (Fig. 1).…”
Section: Bls-flic131 Chimeric Protein Keeps Folding Properties Of Flimentioning
confidence: 73%
“…Afterward, urea was gently removed by stepwise dialysis against Tris–HCl–EDTA buffer containing 4 M urea and then against PBS buffer. The solubilized protein was purified by affinity chromatography using monoclonal anti‐flagellin antibodies . Briefly, the 2B3C5 antibody was conjugated to an activated resin (NHS‐Activated Sepharose 4 Fast Flow G & E) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The work of Fitts et al (1983) confirms at the gene level that the salmonellae constitute a distinct group. Using one strain of S. typhimurium, 10 unique sequences of DNA were isolated that appeared to specifically hybridize with all the Salmonellae examined by the DNA-DNA hybridization technique [20].…”
Section: Introductionmentioning
confidence: 99%